Desenhos de figurinos de Alexandra Exter para Salomé, Romeu e Julieta e Aelita, Rainha de Marte - Abreu, Priscyla Kelly Vieira (2017)
This research covers drawings by the Russian artist Alexandra Exter (1882-1949) for the theater costumes of Salome (1917), Romeo and Juliet (1920) and the science fiction movie Aelita, Queen of Mars (1924). We will make comparative analyzes between Exter's works and works with a thematic focus and visual analogues, mainly from the mid-nineteenth century to the beginning of the twentieth century. The methodological approach is based on researchers such as Carlo Ginsburg and Jorge Coli, who celebrate the studies and practices of Aby Warburg. The purpose is to understand Exter's work both from the avant-garde aspects and from the maintenance of conventional features, whether of content or form. For that, the focus on the visual representation of the female figure became fundamental in this dissertation. We set up the hypothesis that the visual solutions elaborated by Exter for the protagonists of the three works distinguish them from the recurrent representations of these characters, especially through the clothes and gestures.